2011
DOI: 10.1007/s00586-011-1902-7
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of aerobic training in adolescent patients with moderate idiopathic scoliosis

Abstract: Our results suggest that physical activity should be encouraged in scoliotic girls with mild curvatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
5
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
6
5
1
1
Order By: Relevance
“…In our study, both the control group and the AIS group presented R values greater than one, indicating that the test was adequate to evaluate exercise capacity. However, in comparison with healthy individuals, AIS patients had a lower R value, which was similar to that observed in a previous study [22].…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…In our study, both the control group and the AIS group presented R values greater than one, indicating that the test was adequate to evaluate exercise capacity. However, in comparison with healthy individuals, AIS patients had a lower R value, which was similar to that observed in a previous study [22].…”
Section: Discussionsupporting
confidence: 78%
“…In our study, we observed that AIS patients had a decrease in VO2, VO2kg, VE and VT when compared to the control group, as observed in previous studies that also used an incremental exercise protocol [11,12,20,22]. The peak of oxygen consumption is an important indicator of an individual's exercise capacity [23].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations